ANALISIS KOMPARATIF KINERJA KEUANGAN BANK PEMERINTAH DAN BANK ASING DI INDONESIA - Clara Anggraini Sirait; Isfenti Sadalia (Universitas Sumatera Utara, 2013)
Abstract The purpose of this study was to compare and analyze the financial performance of the banks are managed by the Government and the banks are managed by foreign parties in Indonesia. Data collection was performed by collecting secondary data form annual financial reports of Government Bank and Foreign Bank, consisting of the balance sheet and income statement banks period 2009-2011. The method used is descriptive analysis quantitatively using independent sample t-test (t test), with a significance level (α) = 5%. Analyzing data using statistical data processing software SPSS for windows. The results of hypothesis testing by T test showed that of 22 financial ratios studied, only 5 financial ratios, namely the ratio of NIM (Net Interest Margin), BOPO (Beban Operasional terhadap Pendapatan Operasional), PNPL (Provision to Non Performing Loan), LAA (Liquidity Assets to Assets), and LAD (Liquidity Assets to Deposits) showed a significant difference between the financial performance of Government Banks and financial performance of Foreign Banks in Indonesia. Key words : Financial Performance, Government Banks, Foreign Banks, and Bank Financial Ratios